Enhanced microwave absorption property of reduced graphene oxide (RGO)-strontium hexaferrite (SF)/poly (vinylidene) fluoride (PVDF) - Acharya, Sanghamitra; Gopinath, Chinnakonda S.; Alegaonkar, Prashant; Datar, Suwarna (Dimond and Related Materials, 2018)
Enormous growth in the use of electronic gadgets presents a challenge to develop efficient electromagnetic interference (EMI) shielding materials specifically using composites with properties such as light weight and high shielding due to absorption. In the present work we have synthesized a composite material with three components; Reduced Graphene Oxide (RGO) and Strontium Hexaferrite (SrFe12O19) (SF) bound together by polymer Poly (Vinylidene) Fluoride (PVDF). Composite RGO/SF (RGOSF) was prepared by facile one port chemical reduction method. Surface anchoring of similar to 500 nm of magnetic particles over the graphene sheet was confirmed by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Crystal structure of SF particles was analyzed before and after composite formation with RGO. Effective crystallite size was estimated from both XRD and Raman Spectroscopy which showed similar trend moving from SF to RGOSF to RGOSFPVDF. Polymer composite films of RGOSFPVDF were prepared by hot pressing. Both real and imaginary part of magnetic and dielectric parameters were studied. It was observed that enhancement of interfacial polarization and anisotropic heat loss in PVDF matrix was generated by RGOSF which ultimately created more scattering center and helped in absorption of electromagnetic radiation. Critical film thickness of 3 mm was capable to shield up to 33 dB EM energy of which > 99.9% was due to absorption.